Field study and bidimensional numerical simulation of runout and deposition of la marogna rockslide (vicenza, italy) - Tecca, Pia Rosella; Genevois, Rinaldo; Deganutti, Andrea Maria; Dal Prà, Marco (Italian journal of engineering geology and environment, 2013)
<span data-sheets-value="{"1":2,"2":"The study of ancient major rock slope instabilities may help in the detection of the conditions leading to their development, so that consequences and possible prevention and mitigation actions can be envisaged. In this paper, numerical studies have been carried out to recognize the behavior of a rock slope and the kinematics of a rock slide/avalanche in the north-eastern Italian Alps. The “La Marogna” rock avalanche, in the Vicenza Province (Venetian Pre-Alps, North-Eastern Italy), with a volume of about 17x106 m3, still partially dams the narrow valley of the Astico River. Geomorphological investigations highlight that the whole rock avalanche mass is formed by two distinct overlapping bodies and that apparent poor stability conditions characterize the slope above the present main scarp. In order to get indications about triggering factors and present stability conditions, a representative engineering geological model has been built and analyses of the triggering conditions have been performed using the bi-dimensional continuum (FLAC) and discontinuum (UDEC) codes UDEC on the re-constructed original slope profile. Different situations have been simulated for gaining a better understanding of the effect of static and dynamic loads on the modeled rock slope. The numerical results indicate that the effect of a contemporary dynamic loading and joint friction decrease results in the instability of a rock mass limited at its bottom by both bedding and a pre-existing discontinuity"}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">The study of ancient major rock slope instabilities may help in the detection of the conditions leading to their development, so that consequences and possible prevention and mitigation actions can be envisaged. In this paper, numerical studies have been carried out to recognize the behavior of a rock slope and the kinematics of a rock slide/avalanche in the north-eastern Italian Alps. The “La Marogna” rock avalanche, in the Vicenza Province (Venetian Pre-Alps, North-Eastern Italy), with a volume of about 17x106 m3, still partially dams the narrow valley of the Astico River. Geomorphological investigations highlight that the whole rock avalanche mass is formed by two distinct overlapping bodies and that apparent poor stability conditions characterize the slope above the present main scarp. In order to get indications about triggering factors and present stability conditions, a representative engineering geological model has been built and analyses of the triggering conditions have been performed using the bi-dimensional continuum (FLAC) and discontinuum (UDEC) codes UDEC on the re-constructed original slope profile. Different situations have been simulated for gaining a better understanding of the effect of static and dynamic loads on the modeled rock slope. The numerical results indicate that the effect of a contemporary dynamic loading and joint friction decrease results in the instability of a rock mass limited at its bottom by both bedding and a pre-existing discontinuity